2006
DOI: 10.1080/02841850600771486
|View full text |Cite
|
Sign up to set email alerts
|

Role of diffusion-weighted magnetic resonance imaging in diffuse axonal injury

Abstract: DWI cannot detect all DAI-related lesions, but is a potentially useful imaging modality for both diagnosing and assessing patients with DAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 23 publications
(24 reference statements)
0
33
0
5
Order By: Relevance
“…According to Oehmichen et al, 42 localized axonal injury was regularly present in the brains of shaken baby syndrome infants surviving longer than 1.5 to 3.0 hours, but only occasionally in the craniocervical junction. Ezaki et al 43 stated that diffusion-weighted imaging cannot detect all DAI-related lesions but is a potentially useful imaging modality for both diagnosing and assessing patients with DAI.…”
Section: Discussionmentioning
confidence: 99%
“…According to Oehmichen et al, 42 localized axonal injury was regularly present in the brains of shaken baby syndrome infants surviving longer than 1.5 to 3.0 hours, but only occasionally in the craniocervical junction. Ezaki et al 43 stated that diffusion-weighted imaging cannot detect all DAI-related lesions but is a potentially useful imaging modality for both diagnosing and assessing patients with DAI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a need for more sensitive imaging techniques. Several studies have demonstrated the value of diffusion-weighted imaging (DWI) in the evaluation of TAI and other traumatic lesions in the acute stage [2,9,13,14,20,22,30]. In addition to improved lesion detection and characterization DWI could possibly provide clinically relevant quantitative data of traumatic tissue changes away from the visible lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies over the years have advocated different imaging methods to improve identification of DAI-beginning with the standard computed tomography (CT), and moving to general magnetic resonance imaging, or MRI (e.g., Parizel et al, 1998;Tomaiuolo et al, 2005), special sequences of MRI (Takaoka et al, 2002), and finally Diffusion Tensor Imaging (DTI, Ezaki, Tsutsumi, Morikawa, & Nagata, 2006). Each imaging method has been beneficial in improving the number of cases of DAI diagnosed clinically, but still the only definitive diagnostic for DAI is microscopic (Kraus, Susmaras, Caughlin, Walker, Sweeney, & Little, 2007), and autopsy studies in TBI have suggested that DAI is massively underdiagnosed.…”
Section: Diffuse Axonal Injury and Secondary Mechanismsmentioning
confidence: 99%